Exploring therapeutic strategies for androgen-independent prostate cancer using a magnetic coculture platform - Anjani Chavali; Giles Fitzwilliams; Adam Germain; Sandra Khuon; Young-tae Kim (Biomedical Engineering Advances)
Prostate cancer stands as the most diagnosed cancer in males and remains one of the leading causes of death among men in the United States. The progression of prostate cancer to a life-threatening state occurs upon metastasis, typically spreading to vital organs such as the liver, lungs, bones, and lymph nodes, where it sustains growth even in the absence of androgens. In this study, we employed a magnetic coculture device to investigate the interactions between androgen-independent prostate cancer (PC3) cells and healthy normal fibroblasts, aiming to discern their dynamics. Subsequently, the coculture was exposed to varying dosages of Fenbendazole to assess its efficacy differentially on healthy fibroblasts compared to androgen-independent prostate cells. Employing this straightforward coculture method, we observed significant growth, motility, and cluster formation of prostate cancer cells upon direct contact with surrounding fibroblasts. The impact of Fenbendazole was evident in its capacity to markedly diminish the growth and metastasis of prostate cancer cells relative to surrounding fibroblasts. Notably, our findings revealed that a dosage of 2.5 µM Fenbendazole significantly eradicated PC3 cells with minimal damage to surrounding fibroblasts, thus indicating its potential for prostate cancer treatment in-vivo models.